HEMOSTASIS BERLANDASKAN SEL HIDUP (IN VIVO) - Liong Boy Kurniawan; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Understanding of hemostasis has developed substantially in the last century from stasis in vitro to in vivo concept. Hemostasis theory develops from classic theory, discovery of coagulation factors leading to cascade/waterfall theory, as well as to in vivo cell based theory which explains the limitations of cascade theory. Phases of cell based hemostasis theory include initiation, amplification, propagation and termination with the role of tissue factor, platelet activation and coagulation factors in thrombin and fibrin synthesis. Common hemostasis tests used nowadays are important in evaluating bleeding risk but this matter still can not explain cell based hemostasis theory comprehensively so we need to find new tests to evaluate in vivo hemostasis.